The Role of Data Analytics in Global Marketing Decision-Making - Fikta Novia Ayu Safitri (Journal of Mandalika Social Science, 2026)
The increasing availability of digital data and the rapid advancement of digital technologies have transformed marketing from intuition-based practices into evidence-based strategic decision-making. This study aims to analyze and synthesize the strategic role of data analytics in supporting global marketing decision-making among export-oriented small and medium-sized enterprises (SMEs). A qualitative library research approach was employed by critically reviewing and integrating contemporary literature on data analytics, marketing analytics, artificial intelligence, digital transformation, and international marketing. The analysis was conducted through qualitative content analysis and thematic synthesis to identify recurring concepts, compare theoretical perspectives, and develop an integrated conceptual framework. The findings indicate that data analytics has evolved beyond a technological tool into a strategic organizational capability that enables firms to transform diverse data resources into actionable marketing intelligence. By integrating customer insights, predictive analytics, and managerial judgment, organizations can improve market selection, customer segmentation, pricing strategies, promotional planning, and resource allocation in increasingly dynamic international markets. The study further highlights that the effectiveness of data analytics depends not only on technological adoption but also on complementary organizational capabilities, including analytical competencies, digital culture, leadership commitment, organizational learning, and data governance. The principal contribution of this research is the development of an integrated conceptual framework that connects organizational data resources, data analytics capability, strategic marketing intelligence, and global marketing decision-making. This framework provides a comprehensive theoretical foundation for future empirical studies while offering practical insights for managers and policymakers seeking to strengthen the international competitiveness of export-oriented SMEs through data-driven marketing strategies.